Caracterização parcial e patogenicidade de um vírus isolado de Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: geometridae) - Nascimento, Maria de Lourdes [UNESP] (2001)
The present work aimed to characterize a new virus, possibility belonging to CrPV like viruses group, isolated from Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae), the eucalyptus brown looper, and to evaluated its potencial to use as virus bioinsecticide. The experiments were carried out at the laboratory from FCA/UNESP Botucatu - SP and ESALQ/USP Piracicaba- SP. Thyrinteina arnobia virus (TaV) came from sick caterpillars collected in Itatinga, SP in 1996 and in Lençóis Paulista SP in 1997 and colonies were replicated in T. arnobia caterpillars reared in laboratory. The caterpillars mortality from the first to the fourth instar was 100%. Caterpillars infected in the sixth instar and could reach the adult stage showed females with reduced fertility when compared to health ones. Through the survivorship analysis was possible to verify the caterpillars susceptibility to TaV in each T. arnobia instar. All larvae instars exhibited viruses characteristic symptoms. Purified virus suspension samples were observed at the transmission eletronic microscopy and it was visualized a large quantity of picornavirus particles measuring about 30 nm of diameter. Shorter particles with 15 nm were detected, suggesting the existence of satellite virus. The TaV virus cover proteins was serologically detected using antisera produced in rabbit. This cover is composed by three proteins with molecular weight of 47, 60 and 66 kDa. The genomic RNA size varies from 4 to 6 kb. Through ultraslim sections, it was possible to verify that T. arnobia caterpillars infection due to TaV seem to be limited to midgut epithelium, where there has the virions accumulation. The characteristic cytopathic effect was multivesicular bodies formation, apparently due to mitochondrial derivation. Preliminaries assays indicated that TaV did not infect Bombyx mori and Spodoptera... (Complete abstract, click electronic address below).